Analysis of gold precipitation based on point and block kriging - Ali Amri, Nur; ., Winda; Nusanto, Gunawan (International Journal of Engineering and Technology, 2019)
This paper analyzes the prediction of gold distribution in veins using kriging on various block sizes. The empirical semivariogram parameters used are classical and robust, and the models used are weighted least squares and ordinary least squares based on exponential and spherical semivariogram theory. Fitting accuracy is based on the four smallest root mean square errors (RMSE), which are all obtained from the exponential base. An interesting phenomenon occurs in the theoretical exponential semivariogram-based predictions: the average value of block variance is directly proportional to the size of the widely used block. This relationship is also demonstrated by the inverse values of the validation index generated. While linked to the semivariogram parameters, the effectiveness relationship is that the length of the range of the fitting result is inversely related to the acquisition of the meanprediction.Â